1996
DOI: 10.1377/hlthaff.15.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Information Needs: Results of a National Survey

Abstract: A national survey conducted in 1995 found that a disturbingly high percentage of Americans do not understand the basic elements of health plans and that people want much more information, particularly about the physicians in the plans and the range of services that are covered. Their most important concern when selecting a health plan is the quality of physicians in the plan, followed by the courtesy of doctors and staff and the freedom to choose their own doctors and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 0 publications
1
66
0
1
Order By: Relevance
“…This supports Hypothesis 2 and is in line with numerous studies reported in the above literature review, most especially that of Isaacs [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This supports Hypothesis 2 and is in line with numerous studies reported in the above literature review, most especially that of Isaacs [21].…”
Section: Discussionsupporting
confidence: 92%
“…Data presented to them by their employers is treated as suspect as well [22,33]. Distrust is also apparent with regard to information made available via advertising, the media and by way of the government [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of physicians in a plan is by far the most important consideration in choosing a health plan, followed closely by the ability to choose one's own doctors. 3 However, exactly how patients measure quality and which information patients use to make these decisions remains uncertain. 4 Payers tend to measure quality more objectively by focusing on patient admission rates and length of stay, while measuring patient satisfaction by way of survey.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced health-care systems, the role of information has been undisputed, and administrators, scientists, and practitioners continue to find ways to improve the health-care information system (Edgman-Levitan & Cleary, 1996;Isaacs, 1996). In the age of information we live in, health-care information has become even more important in addressing persistent problems of high costs, medical errors, variable quality, administrative inefficiencies, and lack of coordination (Isaacs, 1996;Miller, 1998;Thompson & Brailer, 2004). Hardey (1999) predicts that the Internet as an emerging source of expertise will transform the public use of health information.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%